Multifunction Coffee Table Inspired by Hexagonal Honeycomb - Fatihah Abidin,; Juliana Abdul Halip,; Chumiran, Mohd Hasni (Research in Management of Technology and Business, 2022)
This study is focused on a coffee table that is commonly found in the living room. The country is today dealing with an increase in population leading to the demand for multifunctional furniture, especially for those living in small residential areas. The objectives of this study are to identify the design criteria for a multifunctional coffee table inspired by honeycomb hexagons, to design a multifunction coffee table inspired by honeycomb hexagons and to develop a prototype of a multifunctional coffee table inspired by hexagonal honeycomb. The questionnaires was developed to identify the design criteria of a multi-functional coffee table inspired by honeycomb hexagons was distributed to a total of 100 respondents live at Seremban. The findings obtained from the questionnaire were used to design the sketches (thumbnails, ideation, idea development and final design).Before the prototype manufacturing, the final design was determined by a design survey, and converted into a mock-up and technical drawing. Findings from the questionnaire revealed that preferred design criteria of a coffee table are multifunction with three types of closed compartments, and three units of stool/seat with a combination material. A total of 39 thumbnails sketches were created after the data of design criteria analyzed, ideation and idea development created to produce prototypes and mock-ups of a multifunction coffee table for a living room set inspired by a honeycomb hexagon with a modern aesthetic design based on the thumbnail and ideation sketches delivered.